2015
DOI: 10.1080/09064710.2015.1049653
|View full text |Cite
|
Sign up to set email alerts
|

Aloe veralong-term saline irrigation increases contents of hydrogen peroxide, lipid peroxidation and phenolic compounds

Abstract: Salt stress is more and more becoming a serious problem in the world especially if we consider its damaging effect on the plant growth and yield. The cultivation of medicinal plants, such as Aloe vera, might be an alternative for the saline water use and salt-affected soils occupation. Aloe vera, commonly known as aloe, is one of the primary medicinal plants with multipurpose applications going from pharmaceutical to cosmetic aspects with a promising economic return. Aloe plants were cultivated and irrigated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The genotoxicity of increased salt content may also be attributed to perturbations of the balance between cellular sulphydryl groups and disulphide bonds (Tarin et al, 1996), and the excessive generation of reactive oxygen species (ROS). Several reports showed an overproduction of ROS in plants under saline conditions (Souguir et al, 2015;Wang et al, 2015) which caused damage to cellular structures and macromolecules, especially DNA. A relationship was found between the induction of micronuclei and lipid peroxidation under several stress conditions such as Cd treatment (Souguir et al, 2011;Unyayar et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The genotoxicity of increased salt content may also be attributed to perturbations of the balance between cellular sulphydryl groups and disulphide bonds (Tarin et al, 1996), and the excessive generation of reactive oxygen species (ROS). Several reports showed an overproduction of ROS in plants under saline conditions (Souguir et al, 2015;Wang et al, 2015) which caused damage to cellular structures and macromolecules, especially DNA. A relationship was found between the induction of micronuclei and lipid peroxidation under several stress conditions such as Cd treatment (Souguir et al, 2011;Unyayar et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has also been shown that increased aloe gel concentration and higher ohmic heating (indirectly related to voltage gradient) results in higher electric conductivity of the gel [10]. Both these results suggest that aloe vera gel inherently contains electrolytic ions (such as Ca, K, Mg, and Na [11]) that can be leveraged into developing a more sensitive pressure sensor without adding a large number of external ions.…”
Section: Introductionmentioning
confidence: 89%
“…Salt stress enhances an overproduction of reactive oxygen species (ROS), and this irregularity in ROS causes a remarkable delay in the switch from prophase to pro-metaphase, which influences chromosome separation in anaphase, chromosomal development, and nuclear dynamics (Foreman et al, 2003;Teixeira, 2018). Some reports demonstrated an overproduction of ROS in plants under brackish conditions (Souguir et al, 2015;Wang et al, 2015) which triggered harm cell structures and macromolecules, particularly DNA. Sobieh et al (2019) reported that, with the increase of salt stress there was a significant accumulation of osmoprotectants (proline) and induction of DNA reparations.…”
Section: Mitotic Analysismentioning
confidence: 99%